Optimalisasi Manajemen Perpustakaan: Strategi dan Inovasi untuk Pelayanan Prima - Akhmad Ramli (Departement of Mathematics Education, 2024)
This study focuses on the optimization of library management by exploring strategies and innovations necessary for achieving excellent service. With the rapid evolution of information technology and changing user needs, libraries must adapt to remain relevant and effective. A literature review method was employed to analyze recent scholarly articles, reports, and case studies related to library management. This approach facilitated the identification of best practices and theoretical frameworks pertinent to enhancing library services. The findings reveal several key strategies for optimizing library management, including user engagement, the integration of digital technologies, and ongoing staff training. Additionally, innovative practices such as community-based programs and the implementation of digital services were highlighted as vital to improving user satisfaction. The study underscores the importance of adopting a holistic approach to library management that incorporates strategic planning and innovative practices. These strategies not only enhance service quality but also promote a more responsive library environment. This literature review offers actionable recommendations for library managers, emphasizing the need for continuous adaptation and innovation to meet the evolving demands of users and ensure optimal library performance.